Stem cell factor levels (SCF) in plasma and fibroblast cultures of scleroderma or systemic mastocytosis patients - Zalewska, Anna; Wyczółkowska, Janina; Dziankowska-Bartkowiak, Bożena; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Stem cell factor (SCF) is a pleiotropic cytokine, in the skin released mainly by fibroblasts and endothelial cells. It was demonstrated that SCF exerts stimulatory effect on human mast cells, which are in turn postulated to be involved in pathomechanism of scleroderma, whereas those cells are of key importance in the course of mastocytosis. So, the aim of this study was to evaluate SCF levels in plasma and fibroblast cultures obtained from asleroderma and systemic mastocytosis patients in comparison to healthy controls. The study comprised 20 patients with scleroderma, 20 with mastocytosis and 40 healthy volunteers. SCF levels were measured by ELISA. SCF plasma levels in mastocytosis patients were significantly lower than in scleroderma and the control group (mean ± SD) and were 1335.5±138.6 pg/ml vs 1709.4±494.9 pg/ml (p<0.01) and vs 1592.5±270.2 pg/ml (p 0.05). It was also noted that SCF levels in mastocytosis fibroblast cultures were sugnificantly lower than in scleroderma cultures and were (mean ± SD) 15.8±9.6 pg/ml vs 30.6±16.6 pg/ml (p 0.05). What is more, statistically significant negative correlation between SCF plasma levels in scleroderma patients and severity of the disease assessed by Total Skin Score (TSS) scale together with disease duration was demonstrated (p<0.05). The obtained results point out at some disturbances in SCF in mastocytosis however, they seem not to be of crucial importance either in mastocytosis or in scleroderma development.